Design User Interface dan Program Website Visual Studio pada Alat Pemantauan dan Penyiraman Tanaman Kopi dan Nutrisi Tanah Otomatis Berdasarkan Suhu, Kelembaban, dan Keasaman Berbasis IoT - Taqwiim, Muhammad Ahsani; Hertiana, Sofia Naning; Karna, Nyoman Bogi Aditya (eProceedings of Engineering, 2024)
Indonesia’s geographical conditions are ideal for coffee cultivation, with its tropical climate, fertile soil, and varying elevations. However, challenges such as climate change, remote mountain locations, and less efficient conventional farming methods remain obstacles. This study proposes an Internet of Things (IoT)-based automation system to manage irrigation and soil nutrients for coffee plants in Sukarame Village, Bandung Regency. The solution involves sensors for soil moisture, air temperature, humidity, and soil pH to ensure optimal plant conditions. It utilizes an ESP32 microcontroller, NPK RS485 sensors, and is powered by solar energy with MiFi providing connectivity. Data is transmitted in real-time to a server, enabling remote monitoring. Results demonstrate high sensor accuracy, with 99.91% for Nitrogen, 99.70% for Phosphorus, and 99.80% for Potassium. Implementing this system improves productivity, resource efficiency, and crop quality while supporting sustainable farming practices. Keywords: Coffee Cultivation, ESP32, Internet of Things (IoT), NPK, Website